KARAKTERISASI RESERVOAR MELALUI ANALISIS PETROFISIKA BERDASARKAN DATA LOG SUMUR “TRD” FORMASI AIR BENAKAT - Beny Chasandra; Ordas Dewanto; Ni Putu Juniari (Jurnal Geofisika Eksplorasi, 2018)
The research area was located in South Sumatra Basin on Air Benakat Formation at South-East Jambi Province. The research conducted to know productive the interest zone by petrophysics analysis (volume shale water saturation, and porosity) and its characteristics by well-log. The lithology of TRD Well is sandstone with a few foraminifera. The interpretation based on the petrophysical analysis porosity of the 7th zone on TRD-10 is average 12,4%, saturation water 19,4% and volume shale 6,2%; the 7th zone on TRD-11 well is average porosity 16,2%, saturation water 41,3%, and volume shale 22%; the 11th zone on TRD-14 well is average porosity 33,2%, saturation water 21,2% and volume shale 1,2%; The 6th zone TRD-15 well, porosity 7,02%, saturation water 32,3% and volume shale 5,6%; On the TRD-17 well of the 7th zone is average the porosity 9,04%, saturation water 25,6% and volume shale 4,6%; and 4th zone of TRD-19 well, porosity 23,2% Saturation water 13,5% and volume shale 7,1%. The characteristics of hydrocarbon reservoir on TRD Wells have low water saturation is less than 50%, porosity more than 5% and volume shale less than 25%. From the result of petrophysics parameter value used as the indicator of the productive zone and interpreted that sand reservoir on well TRD has potentially for the reservoir zone with gas prospect.